Intervals of endovascular treatment for coincidental non-adjacent unruptured aneurysms in patients with symptomatic intracranial atherosclerotic stenosis - Jin, Hengwei; Wang, Jing; Meng, Xiangyu; Li, Youxiang; He, Hongwei (Frontiers in Neurology, 2022)
Background and Purpose To explore the safety of endovascular therapy for concomitant non-adjacent unruptured intracranial aneurysms (UIAs) which is incidentally found in severe symptomatic intracranial atherosclerotic stenosis patients at the same session and different sessions. Methods Patients between January, 2019 to December, 2020 were retrospectively reviewed at our institution. Patients with concomitant non-adjacent incidental UIA in severe symptomatic intracranial atherosclerotic stenosis, who underwent endovascular treatment for both lesions were included. They were divided into groups according to the intervals the aneurysm was treated. (the same session as stenosis or separate session). The demographics, procedure details, complications and clinical outcomes were compared between groups. Results A total of 22 patients were involved. Ten patients underwent endovascular treatment for UIA and stenosis at one session and 12 patients at separate sessions. Three (13.6%) patients experienced procedural related complications, including 2(20%) in the one session group and 1(8.3%) in the separate sessions group. Follow-up (Range 6-12, mean=8.5 months) results showed good clinical outcome in all patients. There is no statistical significance in terms of complication rate and unfavorable clinical outcome between groups. Conclusions Non-adjacent concomitant UIA and severe symptomatic intracranial atherosclerotic stenosis will not pose additional endovascular treatment risks. Both simultaneous endovascular management and short intervals between separated procedures are technically feasible and safe.